TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE ERA OF INDEPENDENT CURRICULUM: CREATIVITY OF ISLAMIC RELIGIOUS EDUCATION TEACHER SMAN 2 LUBUK DALAM RIAU PROVINCE - Adi Fernando, Derri; Purnomo, Mulyadi Eko; Oviyanti , Fitri; Maryamah, Maryamah; Meriyanti, Meriyanti (Conciencia, 2024)
This research discusses the transformation of Islamic Religious Education learning in the era of Merdeka Curriculum, focusing on the creativity of Islamic Religious Education teachers at SMAN 2 Lubuk Dalam, Riau Province. This research uses a descriptive qualitative method to describe changes and innovations in teaching Islamic Religious Education. The research subject was the Islamic Education teacher at the school. Data were collected through three main methods: observation, interview, and documentation, to get a comprehensive picture of learning practices. To ensure the validity and credibility of the data, this study used triangulation techniques. The results of the study are expected to provide insight into how Islamic Religious Education teachers adapt and apply creativity in their teaching in accordance with the demands of Merdeka Curriculum or this term is known as differentiated learning.